2021
DOI: 10.3390/geriatrics6010003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exercise Training on Body Temperature in the Elderly: A Retrospective Cohort Study

Abstract: Background: This study evaluated the effect of exercise training on body temperature and clarified the relationship between body temperature and body composition in the elderly. Methods: In this retrospective cohort study, a total of 91 elderly participants performed aerobic and anaerobic exercise training twice a week for 2 years. Non-contact infrared thermometer and bioelectrical impedance analysis were performed at baseline and at 2 years. Results: Mean age of study participants was 81.0 years. The particip… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The mean age in the study group was 81 years. It was found that skeletal muscle mass, rather than metabolic rate or BMI, was strongly associated with an increase in body temperature after two years of exercise training [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mean age in the study group was 81 years. It was found that skeletal muscle mass, rather than metabolic rate or BMI, was strongly associated with an increase in body temperature after two years of exercise training [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study reports that increased body and muscle temperature during exercise will affect metabolism and muscle function [25]. The study was conducted using rats that were trained with a treadmill in different environments, cold acclimatization would increase muscle mitochondria and cytochrome-C oxidase levels were measured [26].…”
Section: Lactic Acid Levels After Recovery Methods Water Temperature ...mentioning
confidence: 99%